Intellectuals in Some Social Theories - Poviliūnas, Arūnas (Problemos, 1996)
The article analyses the set of social theories which interpret intellectuals in different ways. The kernel of the article is two opposing ways of explaining intellectuals’ place in society. A. Gella presents one way. He believes that the main destination of intellectuals’ stratum is the struggle for fundamental socio-political change and active participation in the liberation of the lower classes of a nation from their economic and cultural poverty and or socio-political oppression. The opposing explanation – that intellectuals are the nucleus of the New Class and participate in the struggle for power – is presented by A. W. Gouldner, G. Konrad, and I. Szelenyj. An attempt to find a hidden side of this opposition is made with the help of Z. Bauman’s and P. Bourdieu’s theories. Z. Bauman’s definition of modernity and post-modernity gives one the possibility to situate these opposing explanations. P. Bourdieu proposes an approach, which is based on the fusion of theoretical constructions and empirical investigations, rather than metaphysically speculating on the role of intellectuals.